Jezični slojevi i struktura međimurske hidronimije - Brozović Rončević, Dunja; Virč, Ines (Slavia Centralis, 2020)
The paper examines and describes the hydronymy of Međimurje, the far northern region of Croatia. Field research aimed at the systematic gathering, analysis and classifcation of names of bodies of water throughout Međimurje. The classifcation of hydronyms is based on motivational and word formational criteria, and special attention is paid to the classifcation of hydronyms according to their language of origin. While a complete account of all Međimurje hydronyms is beyond the scope of this paper, the analysis presented here considers the major rivers, streams and lakes, as well as those swamps, springs, ponds and wells whose names are particularly interesting from a linguistic point of view.
Keywords: Međimurje; hidronymy; structural analysis; semantic analysis